2016
DOI: 10.1136/bmjopen-2015-009417
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-2 receptor inhibitors for treating patients with type 2 diabetes mellitus: a systematic review and network meta-analysis

Abstract: ObjectiveBecause of the lack of head-to-head trials, the aim was to indirectly compare sodium glucose transporter-2 (SGLT-2) inhibitors in the treatment of type 2 diabetes.DesignSystematic review and network meta-analysis.Data sourcesMEDLINE and EMBASE were searched from January 2005 to January 2015.Eligibility criteriaRandomised controlled trials assessing the efficacy of SGLT-2 inhibitors in patients with type 2 diabetes inadequately controlled with diet and exercise alone or metformin monotherapy. Minimum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 25 publications
10
88
0
7
Order By: Relevance
“…SGLT2-i are widely studied and several reviews and meta-analyses have recently been published [3436]. Compared to these studies our systematic review with meta-analysis has distinct differences in the dosages and outcomes that we address.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGLT2-i are widely studied and several reviews and meta-analyses have recently been published [3436]. Compared to these studies our systematic review with meta-analysis has distinct differences in the dosages and outcomes that we address.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous meta-analyses evaluating the effects of SGLT2-i in type 2 diabetes, we only included trials, which used the recommended maximum daily doses of the SGLT2-i [2436] as we expect these dosages to be the most widely used in the clinic [4–10]. Lower or higher doses of SGLT2-i might overestimate or underestimate the efficacy or the risk of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Older meta-analyses focused on intermediate outcomes of empagliflozin when compared with placebo; e.g., HbA1c, blood pressure, and body weight (7)(8)(9)(10)(11)(12)(13)(14)(15). The most recent high-quality meta-analyses included 13 (6) and 16 (5) randomized controlled trials (RCTs) that reported mortality and morbidity in adults with type 2 diabetes treated with empagliflozin but did not examine the comparative effectiveness of empagliflozin and other specific antidiabetic drugs (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…A literatura indica um risco maior de infecção urinária e genital na classe das gliflozinas (78), estudos recentes tem indicado também um perfil cardiovascular benéfico para as mesmas (142,144). O custo efetividade das classes ainda precisa ser estudado na população brasileira.…”
Section: Discussionunclassified
“…Até o momento, algumas revisões sistemáticas e metanálises publicadas comparam a eficácia de diferentes fármacos entre as classes das gliptinas e gliflozinas após a falência do tratamento com metformina (71)(72)(73)(74)(75)(76)(77), porém o tempo máximo de análise foi de dois anos (78). Essas duas novas classes terapêuticas recém introduzidas no tratamento para o DM2 precisam de mais estudos, principalmente no que diz respeito ao perfil de segurança e eficácia em longo prazo.…”
Section: A Revisão Sistemática E Metanálise Em Rede Como Ferramenta Dunclassified